2014
DOI: 10.4236/nm.2014.51010
|View full text |Cite
|
Sign up to set email alerts
|

Transcraneal Magnetic Stimulation Improves Sleep Parameters in Patients Affected with Imsomnia Associated to Electroencephalographic Abnormalities

Abstract: Insomnia is one of the most frequently observed sleep disorders, affecting nearly 10% of the general population. It has multiple etiological factors. Recently, it has been reported that EEG abnormalities are associated with insomnia in patients previously diagnosed as idiopathic insomniacs. In addition, transcranial magnetic stimulation (TMS) has shown to be effective in the treatment of disorders characterized by neural hyper-excitability. Method: In the present study, patients with insomnia and EEG abnormali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In combination with PSG and questionnaires, two studies used electroencephalogram (EEG) to examine abnormalities present in patients suffering from chronic insomnia (Sánchez-Escandón et al 2014;Song et al 2019). EEG recordings were done before and after rTMS sessions for comparison.…”
Section: Biological Measurement Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…In combination with PSG and questionnaires, two studies used electroencephalogram (EEG) to examine abnormalities present in patients suffering from chronic insomnia (Sánchez-Escandón et al 2014;Song et al 2019). EEG recordings were done before and after rTMS sessions for comparison.…”
Section: Biological Measurement Outcomesmentioning
confidence: 99%
“…EEG recordings were done before and after rTMS sessions for comparison. In one study the frequency of EEG abnormalities decreased after rTMS treatment while PSG parameters of sleep efficiency and total sleep time improved significantly (Sánchez-Escandón et al 2014). In the other study, EEG recordings of insomnia patients showed over-active or under-active brain regions as compared to healthy controls (Song et al 2019).…”
Section: Biological Measurement Outcomesmentioning
confidence: 99%
“…Importantly, studies assessing the efficacy of rTMS on sleep with objective measurements, for example, PSG, are scarce. In patients with insomnia, rTMS targeted to the frontal cortex resulted in improvements of PSG parameters TST, SE, SOL, and WASO (Sánchez‐Escandón et al., 2014 ), and rTMS targeted to the right dorsolateral prefrontal cortex improved sleep architecture (Jiang et al., 2013 ).…”
Section: Introductionmentioning
confidence: 99%